7-month duration of SARS-CoV-2 mucosal immunoglobulin-A responses and protection - Marking, Ulrika; Bladh, Oscar; Havervall, Sebastian; Svensson, Julia; Greilert-Norin, Nina; Aguilera, Katherina; Kihlgren, Martha; Salomonsson, Ann-Cristin; Månsson, Maja; Gallini, Radiosa; Kriegholm, Cecilia; Bacchus, Philip; et al. (The Lancet infectious diseases, 2023)
Mucosal immunity has a pivotal role in protection from respiratory viral infections.1 The current authors have showed substantial protection from omicron infection by high concentrations of nasal mucosal SARS-CoV-2 WT spike immunoglobulin-A (M-IgA) over a 4-week screening period.2 A sharp increase in M-IgA concentrations following BA.1 or BA.2 breakthrough infection in triple vaccinated health-care workers was also observed.2 Here, we present follow-up data with prospectively collected omicron infection rates and systemic and mucosal antibody concentrations from the same cohort (appendix pp 7–9, 12–14). The association between M-IgA concentrations at the 75th percentile or higher at enrolment and a reduced risk of symptomatic BA.1, BA.2, or BA.5 breakthrough infection remained over an 8-month follow-up period, with a hazard ratio (HR) of 0·55 (95% CI 0·35–0·87), much due to the initial risk difference (figure A). Serum WT spike-specific IgG (S-IgG) concentrations waned over 8 months following a third vaccine dose in all study participants (appendix p 10), concurrent with previous data.3 However, concentrations of nasal M-IgA in participants with previous SARS-CoV-2 infection, but without omicron breakthrough infection, remained above the amount associated to 65% protection2 over the 8-month study period (figure C).